Literatures of Medieval France - Michel Zink (Collège de France, 2017)
This long tradition would certainly not be a reason in itself to keep or restore the subject, had it not something to do with the subject itself. All of the associations between the past and literature, all of the signs that point towards an essential link between the notion of literature and a feeling for the past, are crystallized in medieval literature. The curiosity that medieval literature has aroused since it was rediscovered at the dawn of Romanticism presupposes such associations. The...